Research on vibration fatigue of sensor bracket in a metro bogie based on the pseudo excitation method. (March 2023) - Liu, Kaicheng; Wu, Xingwen; Chi, Maoru; Wen, Zefeng
Highlight: The pseudo-excitation method can reproduce the three-axis vibration level and stress state of the structure. The modal vibration of 61 Hz leads to bracket structural fatigue failure. The rigid-flexible coupled dynamic model is not affected by the wheel-rail relationship and the nonlinearity of suspension elements. The pseudo-excitation method can identify the critical position of the structure in the structural design stage. Abstract: Aiming at investigating on fatigue failure of sensor bracket in a metro bogie, a vibration fatigue assessment method based on the pseudo excitation was proposed in this paper. The fatigue failure mechanism of sensor bracket was primarily investigated through a comprehensive field test, consisting of measuring the frequency response function, acceleration, and dynamic stress of the sensor bracket, as well as the roughness for both rail and wheel. The experimental results showed that the vibration modal near 61 Hz of sensor bracket can be excited by the rail corrugation-induced impact, thereby significantly contributes to stress concentration and increased dynamic stress near the bolt hole of the sensor bracket. To better understand the fatigue failure mechanism and evaluate the fatigue lifetime of the sensor bracket, a rigid-flexible coupled dynamic model of sensor bracket incorporating with the pseudo excitation method was developed to reproduce the vibration level of sensor bracket based on the measured acceleration. This enables us to obtain the full field stress state of sensor bracket, rather than the locations where the strain gauge installed alone. The results indicate that the parent material near the bolt hole of sensor bracket shows the highest damage, which is quite comparable with those observed in the failed sensor bracket.